Karo Batak Local Architecture with its Personal Character to Indonesian National Resilience: (Case Study: Lau Simomo Leprosy Village) - Nuah P Tarigan; Christian Iregar; Petrus Hepi Witono (International Journal of Disabilities and Social Inclusion, 2022)
Indonesian national character is determined by the tribes that are inside, including Karo Bataknese tribes that inhabit the highlands mostly Karo, North Sumatra. Characters tribes is crucial in building national resilience Indonesia, one of the flowers in the garden beautiful Indonesia is diverse. Structural conditions of communities living in the fertile soil but in a long time confined to the cultural conditions that do not support the holistic nature of development and progress. There should be a thorough transformation in the society in order to prevent further epidemic of HIV-AIDS, Leprosy, Tuberculosis and Drugs that have been to some very worrying. The role of local leaders is very important, the role of non-physical culture is also very necessary, including managing physical culture which is increasingly disappearing very rapidly within the community Karo in North Sumatra in particular and Indonesia in general. All members of society should be able to work together effectively again, including the leaders of formal, informal, religious scholars and tribe leaders. Effective leaders need to unite all elements of the community together and focus on the holistic development of Tanah Karo Land. It is unfortunate that the local culture "bronze" non-physical nature has not been optimized carefully, so that the outer buildings that Karo Bataknese architecture is no longer clear to the naked eye. Bronze and architecture should be able to build local resilience that eventually could become a very significant contribution to the Indonesian National Defense, present and future!